ANGKA KEJADIAN FRAKTUR MANDIBULA BERDASARKAN LOKASI ANATOMIS DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI 2011 – DESEMBER 2013 - Dwi Putri, Ratu Astuti; Pamungkas, Kuswan Ambar; Mursali, Laode Burhauddin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTFace is the part of the body that is uncovered topographically and easy to get trauma as the result. The high incidence of traffic accident in developing countries is equal to the increasing of facial bone fracture incidence rate. Anatomy shape and the opened-position of mandibular lead to be easy to get trauma compared to other facial bones. This research was aimed to know the incidence rate of mandibular fracture based on anatomical location in Riau Province General Hospital during January 2011-December 2013 that consists of distribution of mandibular fracture in age, sex, total of fracture line, and trauma variant. The research was an observational study using descriptive retrospective design. This study used total sampling method. Samples of this study were all data of mandibular fracture patient that fulfilled inclusion criteria. The total samples were 206 cases. This study shows that the age group of 18-40 years old (59%) and male (80.1%) in sex group were the most commonly patient with mandibular fracture. Single trauma was the highest trauma that happened with 57.3% in percentage. The highest fracture line was single fracture (68.6%) with symphysis parasymphysis region (26.7%). Symphysis parasymphysis mandibular fracture was found in age group of 18-40 years old (53.12%), male in sex group (75%), single fracture line (63.38), and single trauma in trauma variant (57.81%.) .Keywords: Mandibular Fracture, Anatomical Fracture Location